Avaliação in vitro dos óleos essenciais e compostos majoritários de Lippia alba e Lippia gracilis sobre vermes adultos de Schistosoma mansoni - Gomes, Dharliton Soares (2021)
Schistosomiasis is a waterborne disease caused by trematodes of the genus Schistosoma. Of the most common species that parasitize humans, the most relevant are Schistosoma mansoni, Schistosoma japonicum and Schistosoma haematobium. Of these, S. mansoni is the trematode that causes schistosomiasis mansoni, being the only species found in Brazil. Chemotherapy is currently the most widely used method to combat schistosomiasis, with praziquantel (PZQ) being the drug recommended by the World Health Organization (WHO). Because it is a largescale medication in control programs and because it does not prevent reinfections, there is a concern about the emergence of resistant parasites. Some studies have already demonstrated the efficacy of some species of plants of the genus Lippia against various pathogenic parasites. In this sense, this work aims to evaluate the effect in vitro of essential oils (EOs) of L. alba and L. gracilis and their main components in adult worms of S. mansoni. The extraction of EOs from L. alba and L. gracilis was performed by means of hydrodistillation in a clevenger apparatus and their chemical composition determined by gas chromatography coupled to a mass spectrometer. Couples of adult worms were recovered from mice BALB/c previously infected with the LE strain of S. mansoni. The worms were distributed in 24-well culture plates containing supplemented RPMI-1640 and incubated (37ºC and 5% CO2) in concentrations of 100, 50, 25 and 5 µg/mL of essential oils and major compounds of L. alba and L. gracilis. The worms were monitored for 48 hours at intervals of 2, 4, 8, 24 and 48 hours to assess motility, mortality and oviposition under an inverted microscope. The cytotoxicity of OE and major compounds was evaluated by the MTT assay using mouse fibroblasts. The chemical characterization revealed that the EO of L. alba presents citral (49.97%) and limonene (18.53%) as major compounds, while carvacrol (32.29%), γ-terpinene (20.59%) and ρ-cymene (18.88%) were more abundant in the EO of L. gracilis. Among the tested EOs, L. gracilis was more active, causing a 100% reduction in the viability of worms exposed to concentrations of 100 and 50 µg/mL for 8h. Worms cultured for 24h in the presence of L. alba EO showed a reduction of approximately 60% in their viability at a concentration of 100 µg/mL. Regarding the major compounds, a 100% reduction in worm viability was observed with carvacrol at a concentration of 100µg / mL after 2h; on the other hand, citral reduced the viability of adult worms exposed to concentrations of 50 and 100 µg/mL by more than 75% after 24h. All EOs and their majorities reduced the oviposition of adult worms by more than 90%, even when exposed to a concentration (5 µg/mL) unable to reduce their motility or cause the worms to die. Both EOs proved to be non-toxic at the concentration of 50 µg/mL. The results stimulate future investigations of these plants as a potential source of bioactive compounds against S. mansoni.